The meaning of the local value of Sandeq Boat in the Banggae Community of Majene Regency - Mario; Riri Amandaria; Musrayani Usman (Technium Social Sciences Journal, 2023)
This study aims to find out, how passandeq and the community interpret the local values of sandeq boats today. To achieve this goal, this study uses data collection techniques through observation, interviews, and documentation. The data obtained by researchers from the results of the study were processed by methods used through purposive sampling where the key informant was a passandeq fisherman, then other informants comes from the Banggae community and culturalists. The results showed that the representation of passandeq fishermen and the community towards the local values of sandeq boat culture is still so poorly understood from the meaning of what is described by ancestors in Mandar on sandeq boat culture. The need for the important role of all elements of society to make efforts so that the famous culture in Indonesia from the Mandar tribe is preserved and its meanings Every value in it is able to be conveyed and understood to existing generations. The socio-cultural values of Sandeq boat culture consist of two: first is sibaliparriq which is a gender concept that is more specific in In the family consists of husband and wife. Second, mutual aid at this value is clearly depicted in the sandeq boat where the courtiers and mustard work together in sailing their respective sandeq boatsHave duties and roles when going to sea using Sandeq boats.